Arabic Language Curriculum Management in Mu'ādalah Islamic Boarding School: A Case Study - Dita Puspita Dewi; Ahmad Miftahuddin; Retno Purnama Irawati; Nafis Azmi Amrullah (IJECA (International Journal of Education and Curriculum Application), 2026)
Despite growing scholarly interest in Islamic education, Arabic curriculum management in mu'ādalah boarding schools, particularly century-old institutions with classical scholarly traditions remains underexplored. No comprehensive study has examined how Salafi-style mu'ādalah boarding schools integrate formal curricula with institutionalized language development programs. This study fills this gap by analyzing Arabic curriculum management at Perguruan Islam Mathali'ul Falah (PIM), one of Indonesia's oldest mu'ādalah boarding schools, across planning, implementation, evaluation, and development dimensions. Using qualitative case study methodology, data from institutional leaders, teachers, and 240 students were collected through interviews, observations, questionnaires, and documents, then triangulated across sources and techniques to ensure validity. Miles, Huberman, and Saldaña's (2014) interactive model guided data analysis. Findings reveal a dual-track curriculum model: formal instruction employing naẓariyyah al-waḥdah system with traditional methods, complemented by LPBA's Daurah Arabiyyah extracurricular program, achieving 65–69% student certification. This study contributes the first integrative analytical framework for Arabic curriculum management in Salafi-style mu'ādalah contexts, offering a replicable dual-track model for institutions balancing classical pedagogy with contemporary Arabic competency demands.